2018
DOI: 10.1016/s0140-6736(18)30951-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of renal denervation on blood pressure in the presence of antihypertensive drugs: 6-month efficacy and safety results from the SPYRAL HTN-ON MED proof-of-concept randomised trial

Abstract: Medtronic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
465
4
33

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 638 publications
(551 citation statements)
references
References 38 publications
20
465
4
33
Order By: Relevance
“…The average number of ablations per patient varied from 14 to 45.9 among clinical studies which investigated the effect of branch treatment . Even considering the variation in clinical studies, the number of ablations seems to be smaller in the present study (14.5–17.5) compared with the clinical studies.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…The average number of ablations per patient varied from 14 to 45.9 among clinical studies which investigated the effect of branch treatment . Even considering the variation in clinical studies, the number of ablations seems to be smaller in the present study (14.5–17.5) compared with the clinical studies.…”
Section: Discussioncontrasting
confidence: 57%
“…Importantly, a recent anatomical study showed that the renal sympathetic nerve fibers are distributed closer to the lumen in branch renal arteries (RAs) compared with the main RA, suggesting that RDN that includes the branch RA may ablate more sympathetic nerves than RDN on the main RA alone . This hypothesis was supported in recent animal and clinical studies including the blinded, randomized, sham‐controlled SPYRAL HTN‐OFF MED and ON MED trials . Direct comparison studies in animals and humans clearly confirmed greater efficacy in RDN on both branch and main RA compared with RDN on main RA alone .…”
Section: Introductionmentioning
confidence: 74%
“…Since the first description of the novel technique, numerous studies including randomized and observational trials have demonstrated that catheter‐based RDN resulted in substantial reduction in BP in patients with resistant hypertension . Most recently, three multicenter, randomized, sham‐controlled studies using new generation of RDN device continue to show cogent evidence of significant BP reduction in patients with uncontrolled hypertension …”
Section: Discussionmentioning
confidence: 99%
“…However, the two groups were matched in all baseline characteristics. In addition, the sham effect was absent in recently published sham‐controlled trials including the SPYRAL HTN and RADIANCE‐HTN SOLO . Second, no assessment of ambulatory BP at baseline and at follow‐ups was carried out, which could lead to inclusion of patients with pseudoresistance and whitecoat syndrome.…”
Section: Limitationmentioning
confidence: 99%